Langkah-langkah Menentukan KKM yang Efektif dan Berkualitas - Nurul Jeumpa (Seumike : Society Progress Journal, 2025)
Determining effective and high-quality Minimum Completion Criteria (KKM) is an important aspect in efforts to improve the quality of education in schools. KKM is used as a benchmark to assess student competency achievement in the learning process. This research aims to identify steps that can be taken to establish and implement KKM effectively and with quality. The method used in this research is a qualitative approach with analysis of data obtained through interviews, observation and documentation studies in several schools. The research results show that effective steps in determining KKM include: (1) determining clear learning objectives and in accordance with competency standards, (2) preparing comprehensive assessment criteria, (3) using various varied learning methods and media, (4) continuous evaluation of student progress, and (5) the teacher's active role as a facilitator in helping students achieve the KKM. Apart from that, this research also found that good implementation of KKM requires the involvement of all parties, including teachers, students and parents, in supporting the teaching and learning process. Overall, effective implementation of KKM can help improve the quality of learning and student academic success.